Laser tympanic neurectomy for post-cochlear implant pain: A new technique. (3rd March 2016) - Anand, V.; Kiruthiga Devi, M.; Kannan, T.; Chenniappan, S.
Abstract : Objectives : To present the case histories and management by LASER tympanic neurectomy of two patients who presented with pain as their only symptom after cochlear implantation, avoiding the need for device removal. Clinical presentation : Two of our patients presented with otalgia, which appeared 6 months after cochlear implantation and resulted in their refusing to use the device. The pain was not controlled by repeated remapping or medical management. Neither patient showed evidence of infection or inflammation around their device. X-rays showed that there were no extracochlear electrodes or evidence of extrusion. One patient had current leakage from two electrodes, which were switched off, but the pain persisted. Intervention : Both patients received an intratympanic injection of 1 ml of 0.5% Bupivacaine to anaesthetize the tympanic plexus in the middle ear and were then observed for a day, found to have relief of their pain and were able to use the implant with audiological benefit for this short time, until the effect of the anaesthetic had worn off. Therefore we planned and performed a tympanic neurectomy on both patients using CO2 laser. Conclusion : Tympanic neurectomy removed the pain in two cochlear implant patients who presented with pain which was present only when the implant was switched on.